2018
DOI: 10.1017/s0007114518002933
|View full text |Cite
|
Sign up to set email alerts
|

Associations of breast milk adiponectin, leptin, insulin and ghrelin with maternal characteristics and early infant growth: a longitudinal study

Abstract: Breast milk (BM) hormones have been hypothesised as a nutritional link between maternal and infant metabolic health. This study aimed to evaluate hormone concentrations in BM of women with and without gestational diabetes mellitus (GDM), and the relationship between maternal factors, BM hormones and infant growth. We studied ninety-six nulliparous women with (n 48) and without GDM and their exclusively breastfed term singletons. Women with GDM received dietary therapy or insulin injection for euglycaemia durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
92
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(106 citation statements)
references
References 44 publications
11
92
3
Order By: Relevance
“…There is agreement in the Ghrelin data: Ghrelin levels were found to be lower in colostrum and mature milk, but no differences were observed in transitional milk [17,19,20].…”
Section: Hormonessupporting
confidence: 61%
See 2 more Smart Citations
“…There is agreement in the Ghrelin data: Ghrelin levels were found to be lower in colostrum and mature milk, but no differences were observed in transitional milk [17,19,20].…”
Section: Hormonessupporting
confidence: 61%
“…Another two studies analyzed the HM samples with an ELISA test, but found opposite results. Yu et al showed an increase of insulin levels, not only in mature milk, but also in colostrum in women with GDM, especially in those receiving insulin injections [17]. Nunes et al did not find differences in both types of milk [18].…”
Section: Hormonesmentioning
confidence: 96%
See 1 more Smart Citation
“…As variations in circulating adipokines (18), IGF-1 and cGP (19,20) have been linked to various health and disease outcomes and significant differences in HM hormone concentrations have been described across mother-infant dyads (21)(22)(23), research has focused on associations between hormone concentrations in HM and infant growth outcomes (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). However, while some studies suggest that individual hormonal signatures in HM are associated with different infant growth trajectories, the findings of research in this area remains conflicting (37).…”
Section: Introductionmentioning
confidence: 99%
“…Six articles met the criteria for meta-analysis (19,20,(23)(24)(25)(26). The excluded articles from the study (n=23) included the following: 5 articles presented the effect of breast milk ghrelin on growth in infants (6,18,21,22,27), 8 articles expressed no correlation between infants' serum ghrelin and growth (2, 17, 28-33), 3 articles were of descriptive nature (34-36), and 6 articles had an intervention group (37)(38)(39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 99%